ANALISIS PENGARUH PROFESIONALISME, PENGETAHUAN MENDETEKSI KEKELIRUAN, PENGALAMAN BEKERJA AUDITOR, DAN ETIKA PROFESI TERHADAP PERTIMBANGAN TINGKAT MATERIALITAS AKUNTAN PUBLIK (Studi Empiris Pada Auditor KAP Di Semarang) - Reza Minanda; Dul Muid (Diponegoro Journal of Accounting, 2013)
In order to maintain the trust of clients and users of financial statements, publicaccountants are in demand for more adequate competence. The competence is professionalism,knowledge in detecting errors auditor working experience, professional ethics andconsideration of the materiality of public accounting. The purpose of this study is todemonstrate empirically how much influence the professionalism, knowledge, detecting errors,auditors work experience, and professional ethics to the consideration of the materiality ofpublic accounting. The sample used in this study were 100 respondents that auditors containedin 12 public accounting firm in the city of Semarang. Data were obtained through a surveyquestionnaire completed by senior accountants to partners working in the public accountingfirm located in the city of Semarang. Meanwhile, to answer the research hypotheses using amultiple regression analysis. Based on these results it can be concluded that the variableProfessionalism, Knowledge Detect Errors, Auditor Work Experience, and the Ethicsindividually and jointly significant influence Materiality Level Advisory Public Accountants.